Couples' experiences of pregnancy resulting from assisted reproductive technologies: A qualitative meta-synthesis - Caroline René; Isabelle Landry; Francine de Montigny (Elsevier, 2022)
Background: Across the world, a growing number of couples are directly or indirectly affected by infertility. Advances in assisted reproductive technologies are now enabling many of them to plan to have a child. As pregnancies resulting from assisted reproductive technologies are being experienced by a growing number of couples, it is important to better understand their experiences and the difficulties they encounter during the prenatal period. Objective: This literature review aims to synthesize the qualitative results of primary studies in order to better understand couples' experiences of pregnancy resulting from assisted reproductive technologies, after having experienced infertility. Design: A meta-synthesis was conducted in accordance with the guidelines put forth by Sandelowski and Barroso in order to carry out an integrative analysis of the knowledge resulting from qualitative studies on this phenomenon. Data sources: The literature search was carried out between October and November 2020. Seven electronic databases were searched (CINAHL, Medline, PsycNet, SCOPUS, ScienceDirect, CAIRN, ERUDIT) and 14 eligible articles were selected. Review methods: The data from the "results" and "findings" sections of each of the articles were synthesized through thematic analysis to examine and summarize the topics found in the articles selected and develop the main themes. Results: The thematic analysis is structured around four themes to describe and interpret different aspects of the experience of pregnancy resulting from ART, namely: 1) travelling a long and complex journey; 2) moving on with paradoxical emotions; 3) struggling with an emerging identity; and 4) reorganizing relationships. These results shed light on the complex issues faced by couples previously affected by infertility during a pregnancy resulting from assisted reproductive technologies. Conclusion: The journey of a pregnancy resulting from assisted reproductive technologies must be recognized in order to offer support in line with the challenges faced by couples. This research will allow for a deeper understanding of women's experience, as well as that of their partner's, in a more specific way, and to better understand the impact on family and loved ones.